2016
DOI: 10.2308/accr-51530
|View full text |Cite
|
Sign up to set email alerts
|

Auditors and Client Investment Efficiency

Abstract: This study examines the relation between auditors and their clients' investment efficiency. We hypothesize and find that auditor characteristics that proxy for an auditor's knowledge and resources are associated with higher client investment efficiency, after controlling for the auditor's effect on financial reporting quality. This result is consistent with auditors providing informational advantages to their clients in a generalized investment setting. We find that this auditor effect is more pronounced for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(80 citation statements)
references
References 35 publications
3
67
0
Order By: Relevance
“…Fitzgerald et al (2018) found that internal control reporting quality deteriorates with audit partner tenure. On the other hand, longer-tenured have also positive effects as studies like those conducted by Goldie et al (2018) and Bae et al (2017) documented. However, using hand-collected data from SEC filings, Goldie et al (2018) found that the positive association between reported performance and investment flows is stronger for funds with auditors who are industry specialists and are longer-tenured.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Fitzgerald et al (2018) found that internal control reporting quality deteriorates with audit partner tenure. On the other hand, longer-tenured have also positive effects as studies like those conducted by Goldie et al (2018) and Bae et al (2017) documented. However, using hand-collected data from SEC filings, Goldie et al (2018) found that the positive association between reported performance and investment flows is stronger for funds with auditors who are industry specialists and are longer-tenured.…”
Section: Discussionmentioning
confidence: 85%
“…However, using hand-collected data from SEC filings, Goldie et al (2018) found that the positive association between reported performance and investment flows is stronger for funds with auditors who are industry specialists and are longer-tenured. Bae et al (2017) found that auditor's knowledge and resources are associated with higher client investment efficiency and this effect is more pronounced for clients of longertenured auditors. Francis et al (2017b) suggested that voluntary auditor changes increase information risk, which is due to be priced in private credit markets.…”
Section: Discussionmentioning
confidence: 92%
“…Chen, Xie, and Zhang (2017) focus on the role of financial analysts who provide investors with earnings forecasts of high quality, thereby reducing firms' propensity to over-or under-invest. Finally, Bae, Choi, Dhaliwal, and Lamoreaux (2016) investigate client firms' investment efficiency in the context of auditing literature.…”
Section: A Investment Efficiencymentioning
confidence: 99%
“…Because the client firm benefits from an audit even absent these incentives, we suppress them for simplicity. Bae et al (2017) provide empirical evidence that auditors improve investment efficiency.…”
Section: Baseline Modelmentioning
confidence: 99%